Could the Isle of Man gain from recent innovations in offshore wind?. Issue 4 (July 2016) - Milne, Ken
Abstract : Ken Milne, Director of Energy & Support Services at the Isle of Man Department of Economic Development, discusses some of the developments occurring for the Isle of Man's energy sector.